Toán 7

S

san1201

Ta có [TEX]\frac{1}{2}.(-x+4)=\frac{1}{4}.(\frac{3}{2}x-4)[/TEX]

\Leftrightarrow [TEX]\frac{-x+2}{2}=\frac{\frac{3}{2}x-4}{4}[/TEX]

\Leftrightarrow [TEX]4(-x+4)=2({\frac{3}{2}x-4)[/TEX]

\Leftrightarrow [TEX]16-4x=3x-8[/TEX]

\Leftrightarrow [TEX]7x=24[/TEX]

\Leftrightarrow [TEX]x=\frac{24}{7}[/TEX]

Nhớ thanks nha
 
H

huyenthoaithoca

Ta có [TEX]\frac{1}{2}.(-x+4)=\frac{1}{4}.(\frac{3}{2}x-4)[/TEX]

\Leftrightarrow [TEX]\frac{-x+2}{2}=\frac{\frac{3}{2}x-4}{4}[/TEX]

\Leftrightarrow [TEX]4(-x+4)=2({\frac{3}{2}x-4)[/TEX]

\Leftrightarrow [TEX]16-4x=3x-8[/TEX]

\Leftrightarrow [TEX]7x=24[/TEX]

\Leftrightarrow [TEX]x=\frac{24}{7}[/TEX]

Nhớ thanks nha
Sai rồi : -x+4 và 3/2x-4 là mũ chứ không phải thừa số ????
 
T

thieukhang61

Tìm x : $\dfrac{1}{2}^{(-x+4)}$=$\dfrac{1}{4}^{(\dfrac{3}{2}.x-4)}$ Đề dễ hiểu cần giúp gấp.......
\[\begin{array}{l}
{(\frac{1}{2})^{( - x + 4)}} = {(\frac{1}{4})^{(\frac{3}{2}.x - 4)}}\\
\frac{1}{{{2^{( - x + 4)}}}} = \frac{1}{{{4^{(\frac{3}{2}.x - 4)}}}}\\
= > {2^{( - x + 4)}} = {4^{(\frac{3}{2}.x - 4)}}\\
{4^{(\frac{3}{2}.x - 4)}} = {2^{2(\frac{3}{2}.x - 4)}} = {2^{2.\frac{3}{2}.x - 2.4}} = {2^{3.x - 8}}\\
= > {2^{( - x + 4)}} = {2^{3.x - 8}}\\
= > ( - x) + 4 = 3.x - 8\\
= > 4x = 12\\
= > x = 3
\end{array}\]
 
Top Bottom